2005
DOI: 10.1021/ja044382a
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Micropatterning of Two Different Cell Types

Abstract: The spatial arrangement of individual cell types can now be routinely controlled using soft-lithography-based micropatterning of complementary cell-adhesive and cell-resistant patterns. However, the application of these tools in tissue engineering to recreate tissue complexity in vitro has been hampered by the challenge of finding noncytotoxic procedures for converting complementary cell-resistant regions that define the arrangement of the first cell type into cell-adhesive regions to allow for the attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 12 publications
0
46
1
Order By: Relevance
“…The presence of 10T1/2 did not disrupt the alignment of the C2C12 myotubes, which showed that cell alignment is possible even when two different cell types are present. Several studies have revealed that cell patterning is possible even when two types of cells are present in a culture (Bhatia et al, 1997;Co et al, 2005), but cell alignment under co-culture conditions has not been reported to date. Cell alignment under heterogeneous conditions is especially important in an in vivo environment in which multiple types of cells are present but cell alignment must be maintained.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of 10T1/2 did not disrupt the alignment of the C2C12 myotubes, which showed that cell alignment is possible even when two different cell types are present. Several studies have revealed that cell patterning is possible even when two types of cells are present in a culture (Bhatia et al, 1997;Co et al, 2005), but cell alignment under co-culture conditions has not been reported to date. Cell alignment under heterogeneous conditions is especially important in an in vivo environment in which multiple types of cells are present but cell alignment must be maintained.…”
Section: Discussionmentioning
confidence: 99%
“…By 72 h in culture, these ECs formed extensive cell-cell contact, and linear cellular cords that had hollow central lumen extending several cell lengths. In another study, cell-resistant anionic copolymer of oligoethyleneglycol methacrylate and methacrylic acid was micropatterned on chitosan and gelatin via microcontact printing method, leaving 20 μm wide ECM lines for cell adhesion [59]. Human microvascular ECs cultured on these substrates formed capillary tube-like structures after 5 days.…”
Section: Micropatterning Techniques To Regulate Angiogenesis-micropatmentioning
confidence: 99%
“…They 1) typically require adhesive proteins for cell attachment, [25] 2) are limited to specific parallel geometries defined by laminar flow patterns, [26] or 3) have been used predominantly with cell lines rather than primary cells due to the difficulties involved in attaching primary cells onto synthetic surfaces. [27][28][29][30][31] PEMs have been shown to be excellent candidates for biomaterial applications [31][32][33][34][35][36][37][38][39] and provide flexibility in building complex three-dimensional architectures. [40] The PEM surfaces also provide an ability to control the arrangement of multiple cell types with subcellular resolution.…”
Section: Introductionmentioning
confidence: 99%